The Implementation of Cascade Control Strategy for Liquid Temperature Control on Three Tank Systems using PID Controller - Yuliyanto Agung Prabowo; Hasbi Ashidiqi; Fathammubina; Akhmad Fahruzi (Politeknik Piksi Ganesha Indonesia, 2022)
Controlling the temperature of the liquid in the tank is most widely used in industrial processes. One of the popular systems in industrial processes is the three-tank system. Controlling the temperature directly using the heater element has the disadvantage of a very long transient response and tends to oscillate when there is a set point change. A cascade control strategy is a form of multilevel control consisting of two layers of control loops that allow controlling the temperature by manipulating the level of the liquid. The PID control can be applied in both control layers. Based on the test results, the steady-state time was 27 seconds; while using the direct control method, the steady-state time was slower by 60 minutes.